Assessment of the efficiency of implementation of public-private partnership projects taking into account their life cycles and key stakeholders’ interests - I. Yu. Merzlov (Russian Journal of Economics and Law)
Objective: to develop criteria for objective and comprehensive assessment of the success of public-private partnership (PPP) projects.Methods: in the process of the research, the method of systematic literature review was used.Results: as a result of the study, it was concluded that the success of a PPP project is a relative concept and requires detailing (1) from the viewpoint of which particular stakeholder the project is evaluated and (2) relative to which stage of the project life cycle the assessment is made. This understanding allowed proposing a universal approach to assessing the success of PPP projects, based on the criteria assessment matrix developed by us, which takes into account the stages of the project life cycle and the interests of its stakeholders.Scientific novelty: the systematization of studies available in the Russian and world literature concerning the assessment of the success of both investment projects in general and PPP projects in particular allowed identifying a universal set of criteria for such an assessment. This, in turn, contributes to a more adequate and clear interpretation of the conclusions made by a wide range of authors of research in the field of PPP, who quite often refer to “successful” PPP projects, without giving their own understanding of the criteria for determining success.Practical significance: the developed criteria matrix for assessing the success of PPP projects can become a starting point for improving methodological approaches and normative-legal documents regulating the implementation of PPP projects at the federal and regional levels. Regional and municipal executive authorities planning the implementation of new PPP projects can use the proposed matrix for assessing the success of PPP projects in their work in order, on the one hand, to increase the investment attractiveness of the projects being developed, and on the other hand, to ensure better and objective control over their further implementation.